PENGARUH AGAMA, KEINGINAN BERPINDAH KERJA, KOMITMEN ORGANISASI DAN ETIKA PROFESI TERHADAP PERILAKU PENYIMPANGAN DALAM AUDIT (Studi Empiris Pada Auditor BPKP RI Perwakilan Provinsi Riau) - Monaliza, Monaliza; Hardi, Hardi; Hariadi, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to test empirically and analyze the effect of religiosity,turnover intention, organizational commitment and professional ethics on theacceptance of dysfunctional audit behavior.The data used are primary data inthe form of a questionnaire distributed to the government auditors who work onThe Representative of the Development Finance Comptroller Agency in RiauProvince and a total of 77 auditors. Data analysis method used validity test,reliability test, descriptive statistic test, classical assumption test, multipleregression analysis. The results of this study showed that religy have negative andsignificant impact to the acceptance of dysfunctional audit behavior. Turnoverintention have negative and significant impact to the acceptance of dysfunctionalaudit behavior. organizational commitment have positive and significant impact tothe acceptance of dysfunctional audit behavior. professional ethics have negativeand significant impact to the acceptance of dysfunctional audit behavior.Keywords: religiosity, turnover intention, organizational commitment, professional ethics dysfunctional audit behavior